Geographical Diversions : Tibetan Trade, Global Transactions - Harris, Tina, 1976- (Book collections on Project MUSE., 2013)
Working at the intersections of cultural anthropology, human geography, and material culture, the author explores the social and economic transformations taking place along one trade route that winds its way across China, Nepal, Tibet, and India. How might we make connections between seemingly mundane daily life and more abstract levels of global change? This book focuses on two generations of traders who exchange goods such as sheep wool, pang gdan aprons, and more recently, household appliances. Exploring how traders "make places," the author examines the creation of geographies of trade that work against state ideas of what trade routes should look like. She argues that the tensions between the apparent fixity of national boundaries and the mobility of local individuals around such restrictions are precisely how routes and histories of trade are produced.